DEVELOPING PISA-LIKE MATHEMATICS PROBLEM USING THE 2018 ASIAN GAMES FOOTBALL AND TABLE TENNIS CONTEXT - Nizar, Harisman; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
The objective of this study was to produce valid and practical PISA-like mathematics problems on the content of uncertainty and data using football and table tennis contexts in the 2018 Asian Games. This study also aimed to find out the potential effect of the problems on the tenth-grade students’ mathematical literacy capability of the senior high school. This study was a design research with the type of development studies consisting of two stages, the preliminary and the formative evaluation. We obtained the data using walk-through, document, observation, interview, and test methods. We assessed the validity of the problems by using the validator assessment results towards the content, constructs, and language of the problems and also from the comments/suggestions of the students in one-to-one phase on the clarity/readability of the problems. The indicator of the problems’ practicality was reflected when the students were able to understand the problems well and it was shown in the small group phase. The answers of 33 students involved in the field test showed that the problems had the potential effect, showing the capability of communication and representation. On the problem with football context, six students answered with communication capability and three students with representation capability. On the problem with table tennis context, twenty students answered with communication capability, while five students with representation capability.